GoCas Bag / Nurul Yusniza Manisman … [et al.] - Manisman, Nurul Yusniza; Abdul Latif, Hidayu Natasha; Rahmat, Nur Asna Athirah; Mohamad Nizam, Nurul Izzah Zahiraa; Mohd Khairi, Siti Balqis; Abdullah, Syasya Farhana; Shafiai, Syahiru (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Technological advances in Malaysia have led to various innovations in products and services developed. Nowadays, the use of technology that simplifies business, reduces energy and saves time is very much needed. Devices such as laptops are among the devices that are in demand among university students in performing assignments. Still, the stressful part when leaving home is that we forget to bring a laptop charger or do not charge the laptop with a full battery. Whereas we desperately need it when the laptop is going to die. The innovation against it is the GoCas Bag which is specially designed for university students to use anywhere at any time without carrying a laptop charger or additional socket. The goal of this product is to assist students in charging their laptops, particularly those who use and charge their laptops frequently. The use of a portable and wireless GoCas Bag can make their affairs easier at any time. Functions on the GoCas Bag such as battery percentage indicator to know the percentage of the laptop being charged while protecting the bag from overcharging and damage, on/off light indicator as a laptop fully charged and ready to use, USB port to charge the bag, zip bag function to increase the safety of the bag as well as many compartments for storage of items. With its great functions introduced, it has certainly become a favorite of various individuals.